INVESTIGATION OF NURSING STUDENTS' KNOWLEDGE AND ATTITUDES REGARDING THE METAVERSE - Neşe, Adile; Mihrap İLTER, Sümeyra; BAKIR, Ercan (Göbeklitepe Medical Science Journal, 2024)
Considering the use of Metaverse technologies in healthcare applications today, there is a need to synthesize the perspectives of nursing students towards the use of metaverse in nursing education. This research was conducted in a descriptive manner to examine nursing students' knowledge and attitudes regarding the metaverse. This study was conducted for nursing students at the faculty of health sciences of a state university in Turkey between December 1, 2022, and January 15, 2023. Research data were collected using a questionnaire and metaverse scale. The data was analyzed with the SPSS 25.0 program. 71.2% of the students participating in the study were female, 28.8% were male. It was determined that 43.8% did not know the metaverse and 57.8% thought that the metaverse would have an important place in nursing education and patient care in the future. The total score of the Metaverse scale was determined as 50.94±12.12 (minimum 15-maximum 75 points). It was determined that the metaverse scale average score of nursing students was high.The place where students live, their classroom, the high school they attend, the technological tools they use and the time they spend on the internet were determined as factors affecting their level of knowledge about the metaverse.